2014
DOI: 10.1260/1369-4332.17.8.1199
|View full text |Cite
|
Sign up to set email alerts
|

Control of Seismic Response of a Building Frame by Using Hybrid System with Magnetorheological Dampers and Isolators

Abstract: The traditional isolation approach can suppress the seismic responses of upper structure and at the same time induce substantial deformation of isolation layer. Excessive base drift may cause the degradation and even the damage of the isolation system. Therefore, supplemental control devices can be implemented in the common base isolation system to construct hybrid control system and reduce the base drifts of structures. The seismic mitigation of a building frame with hybrid control system is carried out in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The traditional passive base‐isolation approaches can suppress the seismic responses of the upper structure, but, at the same time, they can induce substantial deformation of the base‐isolation device . An excessive base drift may cause the degradation and even the damage of the base‐isolation system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional passive base‐isolation approaches can suppress the seismic responses of the upper structure, but, at the same time, they can induce substantial deformation of the base‐isolation device . An excessive base drift may cause the degradation and even the damage of the base‐isolation system.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional passive base-isolation approaches can suppress the seismic responses of the upper structure, but, at the same time, they can induce substantial deformation of the base-isolation device. 7 An excessive base drift may cause the degradation and even the damage of the base-isolation system. Therefore, supplemental control devices can be implemented in the common base-isolation system to construct hybrid control systems and reduce the base drifts of structures.…”
Section: Introductionmentioning
confidence: 99%
“…Weber et al [11] studied the performance of structure equipped with a semiactive friction pendulum against the seismic loading and determined the optimal friction coefficient of isolation system for minimizing the structure acceleration. Magnetorheological (MR) damper is also another effective semiactive control system considered separately [12,13] or together with the base isolation system for controlling the structural response [14][15][16][17][18]. Ramallo et al [19] demonstrated the effectiveness of adding a MR damper to conventional isolated structures by achieving notable decreases in base drifts compared to passive systems.…”
Section: Introductionmentioning
confidence: 99%
“…Since the failure of dams incurs great losses to society [1][2][3][4][5], all countries pay careful attention to dam safety, especially to those dams exposed to extreme earthquake loading [6][7][8][9]. In studying the seismic performance of the different types of dam and other civil structural, field surveys [10,11], health monitoring [12,13] and numerical simulation [3,14,15] are important research tools. Computational mechanics has made a strong impact on classical continuum mechanics, which includes engineering and structural mechanics [16][17][18].…”
Section: Introductionmentioning
confidence: 99%